2012
DOI: 10.1016/j.ejrad.2011.01.070
|View full text |Cite
|
Sign up to set email alerts
|

Prospective versus retrospective ECG-gated multislice CT coronary angiography: A systematic review of radiation dose and diagnostic accuracy

Abstract: Purpose: To perform a systematic review of the radiation dose and diagnostic accuracy of prospective versus retrospective ECG-gated multislice CT coronary angiography. Materials and Methods:A search of Pubmed/Medline and Sciencedirect databases for English literature was performed to identify studies comparing prospective and retrospective ECG-gated multislice CT angiography in the diagnosis of coronary artery disease. Effective dose, dose length product, image quality and diagnostic value were compared betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 50 publications
(53 reference statements)
2
46
0
2
Order By: Relevance
“…No bblockers or nitrates were administered for heart rate control or coronary vasodilation. 11 Supplementary unenhanced or delayed acquisitions were performed according to the clinical situation, especially for patients with treated abdominal aortic aneurysm or suspected dissection. But, only arterial phase was used to assess the feasibility of a combined assessment of both the aorta and the coronary arteries.…”
Section: Cta Acquisition Protocolmentioning
confidence: 99%
“…No bblockers or nitrates were administered for heart rate control or coronary vasodilation. 11 Supplementary unenhanced or delayed acquisitions were performed according to the clinical situation, especially for patients with treated abdominal aortic aneurysm or suspected dissection. But, only arterial phase was used to assess the feasibility of a combined assessment of both the aorta and the coronary arteries.…”
Section: Cta Acquisition Protocolmentioning
confidence: 99%
“…(2,3) Although high diagnostic accuracy is achieved with both retrospective and prospective ECG-gated CCTA for detecting CAD (Fig. 1), the radiation doses associated with these two cardiac examinations are significantly different due to the different approaches used for coronary artery scanning.…”
Section: Introductionmentioning
confidence: 99%
“…(2,3) Prospective ECG-gated CCTA also promises high sensitivity (range 93.7%-100.0%), specificity (range 82.7%-97.0%) and NPV (range 95%-98%) in the assessment of CAD. (2,3) Although high diagnostic accuracy is achieved with both retrospective and prospective ECG-gated CCTA for detecting CAD (Fig. 1), the radiation doses associated with these two cardiac examinations are significantly different due to the different approaches used for coronary artery scanning.…”
Section: Introductionmentioning
confidence: 99%
“…18,19,38,39 Table 1 summarizes the diagnostic value of these systematic reviews and meta-analyses of studies performed with CCTA in CAD.…”
mentioning
confidence: 99%
“…8,9,[17][18][19][20] tion, or even the acquisition of whole-heart coverage in one gantry rotation. Two recently reported systematic reviews and meta-analyses further confirmed the high diagnostic accuracy of 320-slice CCTA.…”
mentioning
confidence: 99%